Development of porous material and hybrid porous Ti6Al4V dental implants using metal injection molding (MIM) / Sugeng Supriadi ... [et al.] - Supriadi, Sugeng; Widiantoro, Ana Wilda; Jones, Daniel; Zuhdi, Muhammad Faiq (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Dental implants are biomaterial devices implanted in the jawbone through surgery to replace missing teeth. The surface topography of dental implants with surface roughness and a porous layer made of Ti6Al4V material is recommended to improve osseointegration and induce the growth of new bone tissue (bone ingrowth) while reducing the effect of stress shielding due to the high Young's modulus of the implant material. This study presents the fabrication of porous layers, the development of dental implant design, and the manufacturing process of hybrid porous dental implants using Metal Injection Molding (MIM). Surface analysis was performed on the combination of the implant core material with the porous Ti6AL4V material after the sintering process using a temperature of 1150 °C with holding times of 60, 90, and 120 minutes under an argon atmosphere with a flow rate of 1 liter/minute. The research results showed that the sintering holding time affected the percentage of porosity and hardness of the Ti6Al4V material. Surface roughness greatly influenced the shear bond strength on the surface. The higher the surface roughness value, the higher the shear bond strength. In this study, the highest shear stress value obtained was 1.54 MPa at a surface roughness (Ra) of 2.37 μm. The green part of the hybrid porous dental implant was successfully made using MIM with a mold temperature of 180 °C.